(3OjhGf GSGeI Hf efbPs - (3CHhGdeXaQ GSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHjs; (3CMeO Hf Ydj Hf eMeO Hf NGJeI GdCfUGQj, CHhLYaQs
(3ChdgG (B:s
(3aGffj ZQHJ HfXe GdTYQ aj ZQI GdYeQ adeG YdJ Sfj CcHQJ NWFj hCYXeJg, afOeJ Ydi JaQjWj ajeG fXeJg aMGhdJ Cf CZSd s
(3BNQgG (B:s
(3jfJgj CKfGA bGajI GdgGA Hbhdg(B: (3hbGd HMeU(B: (3jG bdH QabkG HeG CHbjJ ef LdOj ce PG GdMfjf EdCi ef CfJ eKhGg s
(3GfXQ GdLRA GdChd Qbe (B284 (3COHgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B19s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B26 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B775s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdJGQjNs